Family, Failure, and Selfishness In The Movie “Nanti Kita Cerita Tentang Hari Ini” - Erina Wachidatul Insani; Marudut Bernadtua Simanjuntak (Jurnal Pendidikan dan Sastra Inggris, 2022)
The purpose of this study was to observe family problems, failures, and selfishness in the film “Nanti Kita Cerita Tentang Hari Ini” by Marchella FP. This film is an adaptation of the novel of the same name and is released in theaters on January 9, 2020. This research was conducted using a qualitative method and contains several values, especially moral values. This study resulted in three findings. First, family is the most important supporter in life. Second, failure is something that cannot be separated from the journey of life that we go through, even failure can be a life lesson so that we can be better in the future. Third, selfishness is a trait that we should not have because this trait can cause negative impacts on ourselves and those around us. This film tells about a family who seems happy but has many secrets. The main character in this film is named " Awan ". After experiencing her first failure, Awan gets acquainted with a man named "Kale". A man who gives new life experiences, about breaking, getting up, falling, growing, missing, and all the fears of humans in general that leads her to know the secrets that occur in her family.